2017
DOI: 10.3847/1538-4357/aa662f
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Dependence of Stellar Age in Quenched Galaxies at Redshift ∼1.2:Massive Compact Galaxies Are Older than More Extended Ones

Abstract: We report the detection of morphology-dependent stellar age in massive quenched galaxies (QGs) at z ∼ 1.2. The sense of the dependence is that compact QGs are 0.5-2 Gyr older than normal-sized ones. The evidence comes from three different age indicators-D 4000 n , H d ,and fits to spectral synthesis models-applied to their stacked optical spectra. All age indicators consistently show that the stellar populations of compact QGs are older than those of their normal-sized counterparts. We detect weak [O II] emis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 137 publications
(201 reference statements)
6
53
0
Order By: Relevance
“…with observations (Williams et al 2017), as well as its weakening towards higher redshifts (Whitaker et al 2012). In contrast, Furlong et al (2017) found no such trends of galaxy size, neither with sSFR nor with mean stellar age, for massive quenched galaxies in the EAGLE simulation.…”
Section: Comparison Discussionmentioning
confidence: 59%
“…with observations (Williams et al 2017), as well as its weakening towards higher redshifts (Whitaker et al 2012). In contrast, Furlong et al (2017) found no such trends of galaxy size, neither with sSFR nor with mean stellar age, for massive quenched galaxies in the EAGLE simulation.…”
Section: Comparison Discussionmentioning
confidence: 59%
“…Lilly and Carollo (2016) suggested that "progenitor bias" (i.e., the fact that galaxies were smaller and denser in the past) is at least in part responsible for the observed differences between quenched and star-forming galaxies at any epoch. Spectroscopic measures of stellar age at redshift < z 1.5 (Belli et al 2014(Belli et al , 2015Fagioli et al 2016;Williams et al 2017) found that compact galaxies are indeed »1 Gyr older than normally sized ones, adding support to the idea that progenitor bias plays at least some role.…”
Section: Synthesis Of Morphological Trendsmentioning
confidence: 85%
“…At intermediate redshifts (z ∼ 1) previous studies have found conflicting results on the relationship between stellar age and the compactness of passive galaxies, with indications that progenitor bias may be playing a role at this epoch (Keating et al 2015;Williams et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while the majority of high-mass passive galaxies at z ∼ 2 are likely to have been through the ultracompact post-starburst phase (Wild et al 2016), this may become an increasingly less dominant channel towards lower redshifts, when progenitor bias may play a more significant role in explaining size evolution (e.g. see Fagioli et al 2016, Williams et al 2017). Even at low redshift, however, there is evidence that the most compact quiescent galaxies have evolved from post-starburst progenitors (Zahid et al 2016).…”
Section: Discussionmentioning
confidence: 99%